1983
DOI: 10.1111/j.1365-2265.1983.tb00034.x
|View full text |Cite
|
Sign up to set email alerts
|

DETECTION OF THYROID GROWTH IMMUNOGLOBULINS (TGI) BY [3H]‐THYMIDINE INCORPORATION IN CULTURED RAT THYROID FOLLICLES

Abstract: A new bioassay is described for detecting the growth stimulating immunoglobulins (TGI) that contribute to goitre formation in human thyroid autoimmune diseases. It measures the incorporation of tritiated thymidine into intact rat thyroid follicles grown in tissue culture. This radiometric assay demands much less technical skill than the cytochemical bioassays (CBA) previously employed. It has good reproducibility and the techniques and apparatus are available in many clinical laboratories. Immunoglobulins (Igs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
1
1

Year Published

1985
1985
1987
1987

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 16 publications
1
23
1
1
Order By: Relevance
“…This is in contrast to the findings reported using [3H]thymidine incorpora¬ tion assays, although they could detect TGI in a majority of patients who had goitrous Graves' disease, found TGI in only 4:40 (10%) (Chiovato et al 1983) 2:17 (12%) (Valente et al 1983a) and 3:15 (20%) (Schatz et al 1983) of non-toxic goitre. An exception was the report of Rotella et al (1984) who found TGI in 16/30 (53%) with nontoxic simple goitre.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…This is in contrast to the findings reported using [3H]thymidine incorpora¬ tion assays, although they could detect TGI in a majority of patients who had goitrous Graves' disease, found TGI in only 4:40 (10%) (Chiovato et al 1983) 2:17 (12%) (Valente et al 1983a) and 3:15 (20%) (Schatz et al 1983) of non-toxic goitre. An exception was the report of Rotella et al (1984) who found TGI in 16/30 (53%) with nontoxic simple goitre.…”
Section: Discussioncontrasting
confidence: 82%
“…Although the cyto¬ chemical assay system does not have the facility to be applied to the simultaneous measurement of TGI in large numbers of samples as is the case of [3H]thymidine incorporation assays (Chiovato et al 1983;Valente et al 1983a;Schatz et al 1983Schatz et al , 1984 it is considerably more sensitive than these assays. Thus, TGI measured by CBA in the pres¬ ent study was detectable not only in 100% of patients tested who had goitrous Graves' disease or toxic multinodular goitre but in 50% who had hyperthyroidism with autonomously functioning thyroid nodules.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The inhibition by TSH was observed in human thyroid cells (Westermark et al, 1979). The stimulation was observed in rat, guinea pig and dog thyroid cells (Speight et al, 1968;Nitsch and Wollman, 1980b;Drexhage et al, 1980;Drexhage et al, 1981;Chiovato et al, 1983;Roger et al, 1983). In porcine, rabbit and sheep thyroid cells, bovine TSH does not stimulate (Fayet and Hovsepian, 1979;Nilson et al, 1980;Fayet and Hovsepian, 1980;O'Conner et al, 1980;Kaneko, 1981).…”
Section: Discussionmentioning
confidence: 98%
“…Following the pioneering work of Doniach's group (Drexhage et al 1980) several laboratories have validated the hypothesis that goitrous en¬ largement in some thyroid disorders could be induced by autoantibodies mimicking TSH in its growth inducing effect (Chiovato et al 1983;Schatz et al 1983;Valente et al 1983). In these studies, the presence of thyroid growth immuno¬ globulin in the goitrous Graves' disease is parti¬ cularly well documented.…”
mentioning
confidence: 96%